Political institutions and income (re-)distribution: evidence from developed economies - Feld, Lars P.; Schnellenbach, Jan (CESifo working papers, 2013)
We discuss the effect of formal political institutions (electoral systems, fiscal decentralization, presidential and parliamentary regimes) on the extent and direction of income (re-) distribution. Empirical evidence is presented for a large sample of 70 economies and a panel of 13 OECD countries between 1981 and 1998. The evidence indicates that presidential regimes are associated with a less equal distribution of disposable incomes, while electoral systems have no significant effects. Fiscal competition is associated with less income redistribution and a less equal distribution of disposable incomes, but also with a more equal primary income distribution. Our evidence also is in line with earlier empirical contributions that find a positive relationship between trade openness and equality in primary and disposable incomes, as well as the overall redistributive effort.
Keywords: Arbeitspapier; Graue Literatur